Features of determination of middle class in Kazakhstan (The Journal of Psychology and Sociology, 2012)
Topic of the middle class remains one of the most pressing questions of contemporary Kazakh society. This article focuses on the definition of middle class and the identification of criteria to determi-  ne  its representatives in  Kazakhstan. It  provides an  analysis of  different approaches to  define  crite-  ria. Expanding this theme, the author concludes that only the application of multiple criteria simultaneous- ly, a multidimensional approach permits more or less accurately identify social groups that constitute today the Kazakh middle class.
Keywords: middle class; social groups; «comfort class»; approaches to the determination of the middle class; criteria to the middle class.